Dois grandes sítios como alavancas de desenvolvimento regional: - Raimundo Nonato Junior; Hervé Théry (Confins)
This report presents the initial results of the research project "Two major sites as levers for regional development: regional planning around the GSF Pointe du Raz, in Cap Sizun (France) and Ponta Negra, in Natal (Brazil)". It concludes the first stage, which was due to be completed in 2023.